Brazilian journal of science and technology (Springer-Verlag, GmbH, 2014)
Showcases research in the broad field of science and technology (including such disciplines as Agriculture, Biotechnology, Energy Policy, Environmental Studies, Materials Science, and Sustainable Development), with particular respect to Brazil and greater Latin America, but not limited to authorship or topical coverage within the region. The journal explores the dynamics of Research & Development (R & D) under a wide perspective, including not only an emphasis on dissemination of research findings, but also on policy-making and economic growth.
Keywords: Science : Periodicals; Science : Brazil : Periodicals; Technology : Brazil : Periodicals; Science : Latin America : Periodicals; Technology : Latin America : Periodicals; Science; Technology; Brazil; Latin America; Sciences - General